A deconvolution protocol of the mechanical relaxation spectrum to identify and quantify individual polymer feature contributions to self-healing. Issue 19 (7th May 2019) - Montano, Vincenzo; Picken, Stephen J.; van der Zwaag, Sybrand; Garcia, Santiago J.
Abstract : Deconvolution of overlapping relaxation phenomena in near T g intrinsic self-healing polymers. Abstract : Starting from experimental macro-rheological data, we develop a fitting protocol that succeeded in the separation of the overlapping relaxation phenomena in the dissipative regime for a set of intrinsic healing polymers healing most effectively near their glass transition temperature T g . To allow for a proper deconvolution, the rheological master curves are converted to a relaxation spectrum ( H ( τ )) and this is fitted using an optimized mechanical model, e.g. the Maxwell–Weichert model. The deconvolution of overlapping segmental mobility and reversible interactions is successfully demonstrated for a set of polyimide and polyamide polymers containing none, one and two reversible dynamic features near- T g . Through the fitting parameters, the relaxation timescale of each feature and their apparent process enthalpies are obtained. The quantitative data obtained using the fitting protocol are then compared to macroscopic healing results. As a result, a clear correspondence between the energy stored by the system to accomplish reversible ( e.g. H-bonds, π–π) and chain interdiffusion relaxation transitions and the healing efficiency of such polymers are obtained. The implementation of this protocol allows for a clearer identification of the relevant mechanisms in self-healing polymers and paves the way for the development of more efficiently healable polymeric systems.